Protected Agriculture in Mexico - Feng Wu; Zhengfei Guan; Kuan-Ming Huang (EDIS, 2022)
Mexico is a market power in the US produce market. Protected agriculture accelerated the rapid growth and transformation of the Mexican produce industry. This publication provides a comprehensive overview and in-depth analysis of protected agriculture in Mexico to help understand this fast-growing sector and the driving forces behind its expansion.